2020
DOI: 10.2147/amep.s216642
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impact of a Communication Skills Workshop on Doctors’ Behavior Over Time</p>

Abstract: Purpose: Communication skills education is still relatively new in some non-Western countries. Further, most evaluation research on communication skills education examines only short-term results. In our communication skills program in Qatar, we aimed to: 1) assess the impact of the communication skills course on participant skills application; 2) assess the length of time since course completion associated with participant skills application; and 3) assess participant gender or clinical position associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…For instance, most studies (81%) either did not use theories to elaborate on their CPD intervention design (n = 39) or had only explicated their program design in the context of current evidence (n = 44) without using a theory to explain why they believed their CPD intervention would work. Those that incorporated theory, referred to the following: the adult learning theory [16], theory of planned behavior [16], behavior change model [17], implementation change model [18], dual process theory [19], script theory [19], development process theoretical framework [20], social marketing theory [21], apprenticeship model [22], and the Comskil model [14].…”
Section: Evaluation Qualitymentioning
confidence: 99%
“…For instance, most studies (81%) either did not use theories to elaborate on their CPD intervention design (n = 39) or had only explicated their program design in the context of current evidence (n = 44) without using a theory to explain why they believed their CPD intervention would work. Those that incorporated theory, referred to the following: the adult learning theory [16], theory of planned behavior [16], behavior change model [17], implementation change model [18], dual process theory [19], script theory [19], development process theoretical framework [20], social marketing theory [21], apprenticeship model [22], and the Comskil model [14].…”
Section: Evaluation Qualitymentioning
confidence: 99%
“…This study examined whether the time since course completion was related to reported use of communication skills learned during the course. 19 Their results suggest that the impact of the course was sustained over time, with most physicians (92%) being able to name something specific that they had learned from the course and were currently implementing in their practice. Furthermore, the authors point out that knowledge is needed about how doctors, at different levels in their careers, experience postgraduate communication training.…”
Section: Introductionmentioning
confidence: 99%
“…"most evaluation research on communication skills education examines only short-term results". 19 To our knowledge, only one study has explored the impact of postgraduate communication skills training on doctors' behavior over time. This study examined whether the time since course completion was related to reported use of communication skills learned during the course.…”
Section: Introductionmentioning
confidence: 99%
“…Effective communication with patients is a crucial competency of health professionals. 1,2 Poor communication is often linked to patients' misunderstandings, non-adherence to treatments and medical errors. 3 Evidence-based studies showed that effective communication improved patient outcomes and healthcare quality.…”
Section: Introductionmentioning
confidence: 99%
“…Effective communication with patients is a crucial competency of health professionals 1,2 . Poor communication is often linked to patients’ misunderstandings, non‐adherence to treatments and medical errors 3 .…”
Section: Introductionmentioning
confidence: 99%